Принцип встановлення податків і зборів виключно законом та конституційні засади місцевого оподаткування в Україні - Vakaryuk, Lyudmyla; Khudyk, Andrii (Часопис Київського університету права, 2018)
The role of public socially works as a new kind o f administrative penalties is analyzed and researched in this article. Char- acteristic of this charge is given The description o f this penalty is given taking into account the existing practice, the positive and negative aspects o f introducing changes to the legislation in the part o f strengthening the liability o f debtors for non-payment of alimony. Particular attention is paid to the benefits of the new law. / В этой статье осуществлен анализ и исследована роль общественно полезных работ как нового вида административных взысканий. Дана характеристика этому взысканию. С учетом сложившейся практики приведены положительные и отрицательные аспекты введения изменений в законодательство в части усиления ответственности должников за неуплату алиментов. Особое внимание уделено преимуществам нового закона.
Keywords: закон; алименты; аліменти; должники; боржники; law; alimony; debtors; administrative penalty; административное взыскание; адміністративне стягнення; общественно полезные работы; суспільно корисні роботи; socially useful works